2015
DOI: 10.22605/rrh3399
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility and acceptability of administering a telemedicine objective structured clinical exam as a solution for providing equivalent education to remote and rural learners

Abstract: The feasibility and acceptability of administering a telemedicine objective structured clinical exam as a solution for providing equivalent education to remote and rural learners Rural and Remote Health 15: 3399. (Online) 2015

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 9 publications
(8 reference statements)
0
41
0
Order By: Relevance
“…In another study, Shaban et al 13 also found that implementing online OSCE was acceptable by the students and faculty members. This was also highlighted by Palmer et al 19 in a pre-COVID study on the feasibility and acceptability of an online OSCE as well as Kakadia et al 20 in a study on implementing online OSCE during the COVID-19 pandemic. Furthermore, Hamdy et al 14 reported high satisfaction by both medical students and faculty members by the model of virtual clinical encounter examination they designed and implemented as an alternative for traditional OSCE.…”
Section: Discussionmentioning
confidence: 72%
“…In another study, Shaban et al 13 also found that implementing online OSCE was acceptable by the students and faculty members. This was also highlighted by Palmer et al 19 in a pre-COVID study on the feasibility and acceptability of an online OSCE as well as Kakadia et al 20 in a study on implementing online OSCE during the COVID-19 pandemic. Furthermore, Hamdy et al 14 reported high satisfaction by both medical students and faculty members by the model of virtual clinical encounter examination they designed and implemented as an alternative for traditional OSCE.…”
Section: Discussionmentioning
confidence: 72%
“…The use of telemedicine platforms to conduct assessments of competencies such as OSCE has been in place for schools that offer distance learning [12]. In the advent of the COVID-19 pandemic, tele-OSCE was a logical strategy for remote conduct of assessment [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Feasibility promoting factors were defined as factors that enable success of a program through compatibility with available resources (21)(22)(23)(24)(25) and included topic relevancy, preventing attrition/promoting engagement of volunteers, and a leadership/mentorship component.…”
Section: Feasibility Promoting Factorsmentioning
confidence: 99%
“…Furthermore, gauging feasibility before launching a new program is essential for identifying and planning to address logistical challenges (17). Perhaps most importantly, assessing feasibility can help ensure the program is compatible with the available resources of those who intend to implement the training (21)(22)(23)(24)(25). Feasibility is an important aspect to measure given the limited resources most community-based organizations have available.…”
Section: Introductionmentioning
confidence: 99%